HIV testing & diagnosis in 2020 at the apex tertiary referral hospital of India: impact of COVID-19 pandemic. Issue 7 (3rd July 2022) - Maurya, Shesh Prakash; Sharma, Ashutosh; Singh, Ravinder; Gautam, Hitender; Das, Bimal Kumar
ABSTRACT: Timely HIV testing and diagnosis are necessary to prevent the development of AIDS and interrupt its transmission in society. We collected the data on HIV testing and diagnosis in 2020 and compared it with preceding years to examine how COVID-19 pandemic-related restrictions impacted HIV services. The number of people who underwent HIV testing at the apex tertiary referral hospital of India in 2020 reduced by 57% compared to 2019 or the average/year during 2019-2016. Hence, the diagnosis of new HIV infections decreased by 52% compared to 2019 and 54% compared to the average/year during 2019-2016. Provider-initiated testing and diagnosis were more affected than client-initiated. There was a non-significant change in the rate of HIV detection among tested individuals. The male testing saw a more notable drop than female testing. HIV testing between ≥50 years and ≤14 years was more affected than other age groups. The transmission via regular partner/spouse increased, whereas it decreased via heterosexual commercial sex workers.